The Level of Stress among Families of Autistic Children (Raparin Journal of Humanities (RJH), 2025)
Humans experience many pressures، crises، hardships، and obstacles in their lives that can negatively affect their psychological well-being. Psychological stress is a feeling of being under abnormal pressure، which can come from different aspects of daily life (such as increased workload، transitional periods، family arguments، financial difficulties، or having a sick family member). Everyone experiences psychological stress at some point، and people may go through all sorts of nervous situations that are part of daily life.The current era is described as an era of family and psychological pressures، which have become a focus of researchers in psychology، sociology، medicine، and other human sciences. Life changes، and our social roles change with it. We may or may not adapt to these changes، which can lead to psychological distress and reduced personal achievements.This research aims to identify psychological stress among parents of children with autism spectrum disorder in the independent Zakho administration. It also investigates its relationship with several variables (gender، and domains: psychological pressures، social pressures، financial pressures). The research sample consisted of 47 males and 33 females، selected randomly. The researcher used a ready-made psychological stress scale (Al-Suhaimi، 2021) consisting of 15 items with 3 alternatives and adopted a descriptive approach. SPSS was used for data analysis. The results indicated a difference between the two means in favor of the arithmetic mean of the sample individuals، meaning that the sample individuals experience psychological pressures. There was no difference between the mean scores of the research sample individuals in psychological stress according to the gender variable. The mean value for the psychological domain was (13.78)، ranking first، while the third domain ranked last with an arithmetic mean of (7.95). Based on these findings، the researcher presented a set of recommendations and suggestions.